Rasagiline for the symptomatic treatment of fatigue in Parkinson's disease. Issue 13 (November 2015) - Lim, Thien Thien; Kluger, Benzi M.; Rodriguez, Ramon L.; Malaty, Irene A.; Palacio, Rafael; Ojo, Oluwadamilola O.; Patel, Shnehal; Gujrati, Yogesh; Nutter, Benjamin; Swartz, Camille; Hennessy, Carol; Fernandez, Hubert H.
ABSTRACT: Background: Fatigue affects 40% to 50% of all PD patients and is a leading cause of disability, with no clearly established or efficacious established treatments. Methods: In this double‐blinded, placebo‐controlled, pilot trial, we investigated whether rasagiline improved fatigue among PD patients. Subjects were randomized to 1 mg daily of rasagiline or placebo for 12 weeks. The primary endpoint was a change in the Modified Fatigue Impact Scale from baseline to week 12. Results: Thirty PD subjects (16 men), with Modified Fatigue Impact Scale baseline score of 67 ± 15, were randomized (16 to rasagiline vs. 14 to placebo). Significant improvement was noted in the mean Modified Fatigue Impact Scale score of the rasagiline group (12 points) as compared to placebo (8.5 points) from baseline to week 12 ( P = 0.003). Conclusion: In this pilot study, rasagiline at a dose of 1 mg per day improved fatigue. Larger randomized studies are needed to confirm this finding. © 2015 International Parkinson and Movement Disorder Society.